Propositions to Fill for Normative Gaps on Temporary Protection and Refugee Burden Sharing - Ümmühan Elçin Ertuğrul (İstanbul Hukuk Mecmuası)
This paper proposes a paradigm change in the international refugee regime, whereby refugee burden-sharing must shift from state-centrism and security concerns toward a perspective grounded in human rights and the international community. Furthermore, it proposes to fill normative gaps regarding temporary protection and refugee burden-sharing. The right to obtain and receive protection in other countries for a person who is faced with persecution in their own country is a human right However, it does not constitute an international obligation for states under the present refugee regime. Refugee admission is solely under the control and at the discretion of the host states. States usually avoid admitting refugees due to various concerns regarding security, their social and economic situation, and the like. As a result, the refugee burden is placed on the shoulders of just a few states. In fact, it should be shared by all. This paper advocates placing the burden of refugees, including the burden of temporary protection, on the international community as a whole. The argument is that refugee burden-sharing is a jus cogens from which the internationalcommunity as a whole benefits and that jus cogens entails erga omnes obligation for the international community as a whole. In fact, erga omnes obligations may arise even if refugee burden-sharing is not accepted as jus cogens under international law. In discussions on refugee burden-sharing, the logic of collective action and the prisoner’s dilemma have been considered. This paper also contends that burden-sharing states have rights in personam to claim from other states, inspired by Hart’s theory of “mutuality of restriction.” The essence of this paper is based on Friedman’s notion of an everchanging international community and, thus, on an understanding of international law.